Financial stress, monetary policy, and economic activity - Fuchun Li; Pierre St-Amant (Bank of Canada, 2010)
This paper examines empirically the impact of financial stress on the transmission of monetary policy shocks in Canada. The model used is a threshold vector autoregression in which a regime change occurs if financial stress conditions cross a critical threshold. Using the financial stress index developed by Illing and Liu (2006) as a measure of the Canadian financial stress conditions, the authors examine questions such as: Do contractionary and expansionary monetary policy shocks have symmetric effects? Do financial stress conditions play a role as a nonlinear propagator of monetary policy shocks? Does monetary policy have the same effect on the real economy in the low financial stress regime and in the high financial stress regime? Suppose that the economy is currently in a given financial stress regime, do monetary policy shocks have a substantial effect on the transition probability of moving from the given regime to the other? The empirical findings reveal that (i) contractionary monetary shocks typically have a larger effect on output than expansionary monetary shocks; (ii) the effects of large and small shocks are approximately proportional; (iii) expansionary monetary shocks have larger effects on output in the high financial stress regime than in the low financial stress regime; (iv) large expansionary monetary shocks increase the likelihood of moving to, or remaining in, the low financial stress regime; (v) typically, high financial stress regime has been characterized by weaker output growth, higher inflation, and higher interest rates.
Keywords: G01; E50; C01; 330; Financial stability; monetary policy and uncertainty; Geldpolitik; Schock; Transmissionsmechanismus; Inflationsrate; Zinsstruktur; Kanada